1998
DOI: 10.1177/107906329801000302
|View full text |Cite
|
Sign up to set email alerts
|

Treatment May Change Risk Prediction for Sexual Offenders

Abstract: The best predictor of sexual offense recidivism is believed to be past sexual offending. However, clinical observations of treated individuals often contradict this view. Consequently, this relationship was evaluated, using a minimum follow-up period of 18 months. The samples were adult men and consisted of 127 treatment noncompleters who terminated treatment because of inadequate motivation/unacceptable behavior, legal transfer, or by request and 150 treatment completers who underwent a minimum of 6 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…This study, in conjunction with a previous finding that the static variable of prior sex offenses becomes less meaningful in risk prediction after treatment (Studer & Reddon, 1998), reveals the positive effects of some kinds of treatment in mitigating sexual offender recidivism. These types of findings are particularly important in this era of evidence-based practice.…”
Section: Discussionsupporting
confidence: 49%
“…This study, in conjunction with a previous finding that the static variable of prior sex offenses becomes less meaningful in risk prediction after treatment (Studer & Reddon, 1998), reveals the positive effects of some kinds of treatment in mitigating sexual offender recidivism. These types of findings are particularly important in this era of evidence-based practice.…”
Section: Discussionsupporting
confidence: 49%
“…Studer and Reddon (1998) found that a reliable historical predictor, prior sexual offenses, did not predict sexual recidivism among offenders who had completed treatment but was a strong predictor of subsequent sexual recidivism among treatment noncompleters, that is, men who had terminated treatment owing to inadequate motivation or unacceptable behavior. It is assumed that treatment noncompleters did not demonstrate substantial reduction in risk, but no specific measure of change in sex offending risk was undertaken by these authors.…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, the literature evaluating treatment outcomes has lagged behind the recognition of this clinical phenomenon and the resulting development and implementation of programs to address JSOs. As a result, while research shows that lack of successful treatment predicts higher rates of recidivism (e.g., Studer & Reddon, 1998), little is known about what "successful treatment" entails. Further, intra-and interpersonal, demographic, and other variables that impact treatment have not been well established.…”
Section: Discussionmentioning
confidence: 94%